Pengembangan Bahasa Inggris Melalui Metode “Si Ular dan Si Elang” - Mohammad Halili; Darul Hikmah; Sriyono Sriyono (LPPM Universitas Trunojoyo Madura, 2021)
The community engagement activity is specifically designed to discover the impact of “The Snake” and “The Eagle” method in enhancing the teachers’ competence in English language teaching and learning. Contextually, the teaching method is closely related to the achievement of the goals of the teaching itself. Considering the importance of teaching approach, designing the class activities remains essential. This approach is considered to be simple and easy to internalize English learning materials such as new vocabularies and tenses, past tense for example. Therefore, the current research aims to discover how the implemented approach carries influencing outcomes to learning English. This activity engaged a number of English teachers in Pangongsean, Patapan, Bringin Nunggal villages in Torjun Sub-District, Sampang District. To reveal its impacts, we invited the English teachers in the given areas to engage in this practice so as to they are well informed about this teaching method. We also invited some students to have direct practices after the method insights given. Later, we did interview with English teachers to get to know how the teaching method would be useful in their context. Research shows that the method remains both useful and applicative for English teachers’ competence in teaching English. The other sides of the current research are the challenges faced. The students’ lack of vocabularies and low level of their motivation are problematic. In addition, having more time to practice the method is required so that we can give more room to both teachers and students to have more fun learning by using “Si Ular” dan “Si Elang” method in learning English.